The interaction of syntax, semantics & pragmatics in grammars: the development of analytic tools in modern linguistics - Van Valin Junior, Robert D. (ALFA: Revista de Linguística, 2001)
One of the primary tasks facing a grammatical theory is to capture the interaction of syntax, semantics and pragmatics in linguistic systems. This is essential if linguistic theory is to explain the communicative functions of grammatical structures in particular languages and across languages. The questions which must be answered include: what is the appropriate universally valid representation for syntactic structure?, what would be an adequate representation of crucial aspects of the semantics of propositions?, how can discourse-pragmatic information be represented in a grammatically relevant way, and, most important, how do these different representations interact with each other? In this paper answers to these questions will be given in terms of Role and Reference Grammar (Van Valin, 1993; Van Valin & La Polla, 1997).